Masking and Unmasking of Isolated Noncompaction of the Left Ventricle With Real-Time Contrast Echocardiography. (November 2017) - Aggarwal, Sourabh; Xie, Feng; Porter, Thomas R.
Abstract : Supplemental Digital Content is available in the text.